Location-based games as a contemporary, original, and innovative method of seniors’ teaching and learning - Jurczyk-Romanowska, Ewa; Koszczyc, Marta; Jakubowska, Luba; Marcinkiewicz-Wilk, Aleksandra; Gulanowski, Jacek; Kabát, Michał; Švecová, Magdaléna; Milenkovic Jankovic, Tijana; Barone, Paola; Giannelaki, Charoula; Žemaitaitytė, Irena; Katkonienė, Agata; et al. (University of Wroclaw. Department of Pedagogy, 2019)
The handbook consists of three parts. The first chapter provides a diagnosis of older people and their competence in new technologies. This chapter also describes the ICT education programmes for older people available in the partner countries. The next chapter contains a description and results of a pedagogical experiment aimed at comparing the effectiveness of the method of teaching seniors how to use smartphones. The experiment compared the class and lesson method, which dominates the educational offer addressed to seniors, with the method consistent with the strategy of edutainment – a location-based game. The last part contains scenarios of classes dedicated to the method of location-based games as well as traditional classes and classroom games. The handbook presented to the Reader may be an interesting position for practitioners dealing with andragogy, education of the elderly or ICT education, as it contains ready-made educational programs that can be directly implemented in their own practice related to the education of seniors. It is also worth noting that the results of the conducted research significantly enrich the area of andragogy and didactics, showing location-based games as an effective method of learning.
Keywords: seniors; andragogy; seniors' learning; seniors' teaching; location-based games; edutainment